2007
DOI: 10.1021/es0624063
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Water-Soluble Heavy Crude Oil Organic-Acids, Bases, and Neutrals by Electrospray Ionization and Field Desorption Ionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: We identify water-soluble (23 degrees C) crude oil NSO nonvolatile acidic, basic, and neutral crude oil hydrocarbons by negative-ion ESI and continuous flow FD FT-ICR MS at an average mass resolving power, m/deltam50% = 550,000. Of the 7000+ singly charged acidic species identified in South American crude oil, surprisingly, many are water-soluble, and much more so in pure water than in seawater. The truncated m/z distributions for water-soluble components exhibit preferential molecular weight, size, and hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
167
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(177 citation statements)
references
References 38 publications
10
167
0
Order By: Relevance
“…Interestingly, the O 2 class (presumably carboxylic acids) are not aromatic because their DBE values are typically 4 or less (and the simplest aromatic carboxylic acid would have DBE ϭ 5). Plots of DBE vs. carbon number have proved especially useful in characterizing hydrotreatment in petroleum processing (22)(23)(24), vacuum gas oil distillation cuts (25), water-soluble acids and bases (26), saturates vs. aromatics (27), heat exchanger deposits (28), oil:water emulsion interfacial material (29-31), (lack of) matrix effects in saturates/aromatics/ resins/asphaltenes (SARA) (32) fractionation (33), naphthenic acids (1, 34, 35), sulfur-containing polycyclic aromatics (27,(36)(37)(38), distillates (39,40), and other applications discussed in this article.…”
Section: Compositional Sorting: Graphical Images Derived From Heteroatommentioning
confidence: 99%
“…Interestingly, the O 2 class (presumably carboxylic acids) are not aromatic because their DBE values are typically 4 or less (and the simplest aromatic carboxylic acid would have DBE ϭ 5). Plots of DBE vs. carbon number have proved especially useful in characterizing hydrotreatment in petroleum processing (22)(23)(24), vacuum gas oil distillation cuts (25), water-soluble acids and bases (26), saturates vs. aromatics (27), heat exchanger deposits (28), oil:water emulsion interfacial material (29-31), (lack of) matrix effects in saturates/aromatics/ resins/asphaltenes (SARA) (32) fractionation (33), naphthenic acids (1, 34, 35), sulfur-containing polycyclic aromatics (27,(36)(37)(38), distillates (39,40), and other applications discussed in this article.…”
Section: Compositional Sorting: Graphical Images Derived From Heteroatommentioning
confidence: 99%
“…The current study was carried out in controlled laboratory conditions so that direct observation of photochemical transformations of oil composition could be observed. Previous studies have targeted oil molecules that partition into water (water soluble organics, WSO) [22][23][24]. Stanford et al identified molecular formulas of water-soluble species present in South American and Medium Arabian crude oils by FT-ICR MS [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have targeted oil molecules that partition into water (water soluble organics, WSO) [22][23][24]. Stanford et al identified molecular formulas of water-soluble species present in South American and Medium Arabian crude oils by FT-ICR MS [24]. Fathalla and Andersson observed formation of oxygenated products upon irradiation of polycyclic aromatic sulfur heterocycle oil fractions [25].…”
Section: Introductionmentioning
confidence: 99%
“…While the determination of volatile and non-polar components has been achieved by gas chromatography/mass spectrometry (GC/MS), the identification of trace polar components in crude oil is performed using liquid chromatography/mass spectrometry (LC/MS) [8]. Mass spectrometric ionization techniques, namely, electron impact ionization (EI) [9], field ionization (FI) [10], and field desorption (FD) [11] are sufficient for analysis of volatile and semi volatile compounds in crude oil [8]. For the analysis of the compounds with higher boiling points, producing characteristic fragments, pyrolysis/mass spectrometry (Py/MS) or pyrolysis/gas chromatography/mass spectrometry (Py/GC/MS) needs to be considered [12].…”
Section: Introductionmentioning
confidence: 99%